Growth curves of fodder cereals. Loat (Avena sativa L.) (Semiárida, 2020)
The trial was carried out to study dry matter yields of 6 oat (Avena sativa L.) cultivars, and the seasonal growth distribution. Green standing crop was clipped every 7 days in 90 plots arranged at random in 5 series with 3 repetitions each. The environmental conditions determined a very short growing period, principally in early cultivars. Significant differences (P < 0,05) were observed between Millauquén INTA (2,164.0 kg MS/ha) and 82/2866 Sv. and Suregrain cultivars (1,431.5 and 1,464.8 kg MS/ha, respectively). The growth equations of each cultivar was determined. The highest growth rate (28.54 kg MS/ha/day) corresponded to Millauquén INTA, and was shown at early june. Millauquén INTA, Sra. 74/76864 and Moregrain showed a better dry matter distribution than the resto during the entire growth season.
Keywords: oat; production; growth curves